Cyclic Behavior of Reinforced Welded Flange Plate Moment Connections with Triangular stiffener Plates - Seyed Mohammadreza Farooghimehr (Iranian Society of Structrual Engineering (ISSE), 2019)
Regarding the importance of seismic performance and also the problems of moment connections, representing an accurate and efficient scheme to reinforcing could be useful to eliminate these problems. Assuming that (CJP) welds between top flange plate and column face have poor quality or strengthened like fillet welds, the need of reinforcing becomes obvious. For that reason, by using triangular stiffener plate for joining to column face and top flange plate, the seismic behavior could be improved and possible to opt as a reinforcing scheme. To prove that, the experimental specimen was created and investigated. Then, validation was employed with the numerical model of one. By applying the basic concepts of the mechanic of materials, the design of triangular plate was expressed. Along with that, sensitivity analysis with studying on several numerical models carried out to show the accuracy of the proposal procedure design. Moreover, some factors effect on the seismic behavior of this scheme including numbers of stiffener plate, the thickness of stiffener plate, and the width to thickness ratio of box column. While using the box column in literature is rare, it replaces with H-shape column mostly in some countries like Iran. So, this paper tries to consider these cases to cover all aspects of this reinforcing scheme. The results showed this procedure could enhance the seismic behavior of defective moment connections.